An Assessment on the Structure of Shariah Audit Function: The Case of Malaysian Takaful Industry - Noor Aimi Mohamad Puad; Nurdianawati Irwani Abdullah; Zurina Shafii (IIUM, 2024)
Vol. 11 No. 2 Page (161-173)